Daphnia magna, a Host for Evaluation of Bacterial Virulence - Le Coadic, Marion (American Society for Microbiology, 2012)
We show that Daphnia magna can be used to assess acute virulence of pathogens relevant to human health, such as Pseudomonas aeruginosa or Photorhabdus asymbiotica. Analysis of bacterial mutants suggests that P. aeruginosa uses similar mechanisms to infect Daphnia and other hosts.